Growth pole theory and economic development - Buttler, Friedrich (Farnborough, Hants. : Saxon House ; Lexington, Mass. : Lexington Books, 1975)
This volume is split in three parts. Part 1 discusses assumptions regarding sectorial and regional polarization. Part 2 examines the regional development policy in Spain since 1964. The final part gives examples of the Spanish growth poles (Huelva and Seville).
Revised version of Entwicklungspole und räumliches Wirtschaftswachstum.
Includes index.
Includes bibliographical references: p. 215-224.
ne 24/01/2019
Loans
Keywords: Economic development; Regional planning; Central places